2012
DOI: 10.1189/jlb.0611289
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting Mer receptor tyrosine kinase suppresses STAT1, SOCS1/3, and NF-κB activation and enhances inflammatory responses in lipopolysaccharide-induced acute lung injury

Abstract: Mer signaling participates in a novel inhibitory pathway in TLR activation. The purpose of the present study was to examine the role of Mer signaling in the down-regulation of TLR4 activation-driven immune responses in mice, i.t.-treated with LPS, using the specific Mer-blocking antibody. At 4 h and 24 h after LPS treatment, expression of Mer protein in alveolar macrophages and lung tissue decreased, sMer in BALF increased significantly, and Mer activation increased. Pretreatment with anti-Mer antibody did not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
72
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 46 publications
6
72
1
Order By: Relevance
“…TAPI-0 is a peptide-based compound in which the hydroxamic group (a strong chelating moiety) interacts with the catalytic zinc of the ADAM family of proteases and consequently inhibits their activities (Balakrishnan et al, 2006;Antczak et al, 2008). Consistently, we found that in vivo exposure of lungs to LPS enhanced the production of soluble Mer protein (sMer) but decreased membrane-bound Mer expression in alveolar macrophages in spite of increased Mer mRNA expression (Lee et al, 2012a). ADAMs, including ADAM17, also known as tumor necrosis factor-a (TNF-a)-converting enzyme, and ADAM10, are involved in normal processes such as wound repair and tissue remodeling.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…TAPI-0 is a peptide-based compound in which the hydroxamic group (a strong chelating moiety) interacts with the catalytic zinc of the ADAM family of proteases and consequently inhibits their activities (Balakrishnan et al, 2006;Antczak et al, 2008). Consistently, we found that in vivo exposure of lungs to LPS enhanced the production of soluble Mer protein (sMer) but decreased membrane-bound Mer expression in alveolar macrophages in spite of increased Mer mRNA expression (Lee et al, 2012a). ADAMs, including ADAM17, also known as tumor necrosis factor-a (TNF-a)-converting enzyme, and ADAM10, are involved in normal processes such as wound repair and tissue remodeling.…”
Section: Introductionsupporting
confidence: 68%
“…In addition, Mer mediates the induction of phosphorylation of cytoskeletal proteins p130cas and FAK, which have been previously implicated in apoptotic cell phagocytosis (Wu et al, 2005;Singh et al, 2007). Previously, our in vivo study found that blocking the interaction of Mer with its ligand using antiMer neutralizing antibody results in decreased LPS-induced Mer activation (given that full-length Mer protein expression is suppressed) as well as downstream signaling (Lee et al, 2012a). In the present study, changes in the activation of these downstream molecules in lung tissue after TAPI-0 treatment were examined.…”
Section: Tapi-0 Treatment Reduces Smer Production Andmentioning
confidence: 64%
See 1 more Smart Citation
“…MerTK engagement triggers AC internalization via cytoskeletal signaling, and it also activates an anti-inflammatory response by suppressing NF-κB (15,16). As such, MerTK knockout mice develop a lupus-like phenotype in aged mice (17), demonstrate accelerated atherosclerosis in hypercholesterolemic mice due to defective clearance of ACs and heightened inflammation (18,19), and have increased peritonitis in response to a sterile inflammatory stimulus (20).…”
Section: -Lipoxygenasementioning
confidence: 99%
“…Indeed, in chronic active lesions from patients with multiple sclerosis, it has been shown that the increase in the soluble forms of these receptors due to augmented ADAM17 activity is associated with a sequestration of Gas6 and subsequent increased inflammation [14]. In a mouse model of inflammation, exposure of lungs to lipopolysaccharide (LPS) enhanced the production of soluble Mer [15], whereas the upregulation of membrane Mer was able to prevent the inflammatory cascade during lung injury [16].…”
mentioning
confidence: 99%